Epidemiology and inflammatory bowel diseases - El-Tawil, Ahmed Mahmoud (Baishideng Publishing Group Co., Limited, 2013)
The role of alcohol in causing or aggravating the pathogenesis of inflammatory bowel disease is unclear. For finding a conclusive answer for this valuable question we conducted this review. Only two studies were identified that successfully fulfilled our inclusive criteria. Usual consumption of alcohol reduced the risk compared with less frequent use (odds ratio = 0.57, 95%CI: 0.37-0.86). Light alcoholic drinking has protective effects against development of ulcerative colitis. But this inverse association disappeared when smoking was included.